Business Process Re-engineering, and its Possible Applications for Improving the Libyan Banking Sector (The International Journal of Engineering & Information Technology (IJEIT), 2024)
his paper investigates the possibility forimproving the performance level within the Libyanbanking sector. A survey methodology was used forthis study, along with customers’ observations andone-to-one interviews with a couple of decision makersand executive managers within the Jamhouriya Bank,investigating the current status for adapting theprinciples of Business Process Re-engineering (BPR).Based on the data analysis, the findings show thatBPR is widely accepted by majority of theparticipants, whereas, the working environment needsto be prepared for adapting the BPR conceptsthroughout the entire banking operations, specificallythe electronic services such as ATM cards. Thefinding also indicates that, improvements in theperformance levels of the banking operations leads toimproving the customer services in terms of costreduction and fast services delivery. On the otherhand, the results also pointed out that the surveyedorganizations do not pay that much attention to someCritical Success Factors that being considered ascrucial to implement BPR successfully. So, as a firststep for efficiently adapting BPR, the most importantissue is to ensure the top management support andallocating all the necessary resources. Only thenincreased customer satisfaction along with theprofitability can be guaranteed within the Libyanbanking business area